Study on the cold tolerance of maize (Zea mays L.) inbred lines in Phytotron - Csepregi-Heilmann, Eszter; Áldott-Sipos, Ágnes; Mészáros, Anita; Kovács, Anett Klaudia; Spitko, Tamás; Szőke, Csaba; Pintér, János; Berzy, Tamás; Széles, Adrienn; Marton, Csaba L. (Acta Agraria Debreceniensis, 2023)
Maize has come a long way from the tropics to the temperate zone. In the beginning, the spreading of maize was prevented by its sensitivity to cold. Improved cold tolerance at germination is one of the most important conditions for early sowing. The advantage of cold tolerant hybrids is that they can be sown earlier, allowing longer growing seasons and higher yields, due to the fact that the most sensitive period in terms of water requirements, flowering, takes place earlier, i.e. before the onset of summer drought and heat. In Martonvásár, continuous research is carried out to improve the cold tolerance of maize. In the present experiment, the cold tolerance of 30 genetically different maize inbred lines was investigated in a Phytotron climate chamber (PGV-36). The aim of our research is to identify cold tolerant lines that can be used as parental components to produce proper cold tolerant hybrids and/or as sources of starting materials for new cold tolerant inbred lines. After observing and evaluating changes in phenological traits under cold-test, the results of the cold-tolerance traits of interest have been used to highlight several inbred lines that could be good starting materials for further research on genetic selection for cold tolerance.